2006
DOI: 10.3201/eid1203.050560
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Fluoroquinolone-resistantSalmonellaParatyphi A Isolate, India

Abstract: Salmonella enterica serovar Paratyphi A is increasingly a cause of enteric fever. Sequence analysis of an Indian isolate showed a unique strain with high-level resistance to ciprofloxacin associated with double mutations in the DNA gyrase subunit gyrA (Ser83→Phe and Asp87→Gly) and a mutation in topoisomerase IV subunit parC (Ser80→Arg).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…Mutations in gyrA outside of the QRDR were observed both in NAL R and NAL S isolates (data not shown). These data are in full agreement with the data of Nair et al [14] who demonstrated that a single gyrA mutation at Ser-83 alone resulted in resistance to nalidixic acid and reduced susceptibility to ciprofloxacin (MICs of 0.125-0.25 g/mL). Therefore, it was concluded that Ser-83 is an important site for determining fluoroquinolone resistance within S. Typhi and S. Paratyphi A isolates.…”
Section: Resultssupporting
confidence: 92%
“…Mutations in gyrA outside of the QRDR were observed both in NAL R and NAL S isolates (data not shown). These data are in full agreement with the data of Nair et al [14] who demonstrated that a single gyrA mutation at Ser-83 alone resulted in resistance to nalidixic acid and reduced susceptibility to ciprofloxacin (MICs of 0.125-0.25 g/mL). Therefore, it was concluded that Ser-83 is an important site for determining fluoroquinolone resistance within S. Typhi and S. Paratyphi A isolates.…”
Section: Resultssupporting
confidence: 92%
“…Quinolone‐resistant Sal 4 isolates presented the parC (S80R) and gyrA (S83F, D87G) mutations that contributed to ciprofloxacin resistance, our findings were similar to those reported previously (Hopkins, Davies, & Threlfall, ; Nair et al, ). We have found five novel parC mutations including A628S, T255S, N395S, S469A, and A620T.…”
Section: Discussionsupporting
confidence: 91%
“…The primers used to detect qnr plasmids (5) were: 5′-GGG TAT GGA TAT TAT TGA TAAG-3′ for qnr A and 5′-CTA ATC CGGG CAG CAC TAT TAT-3′ for qnr B and 5′- GTGAATTATTGCGGAATCCAGC for AAC1-F as described by Wang et al [22] and Nair et al [4]. PCR and sequencing using the aforementioned primers was performed according to Mammeri et al [23].…”
Section: Methodsmentioning
confidence: 99%
“…Recent literature cites isolated reports of high-level ciprofloxacin resistance in enteric fever, from India and elsewhere [1318]. Studies on molecular analysis of fluoroquinolone resistance in clinical isolates of Salmonella enterica serotype Typhi and Paratyphi A from India are limited [2, 4, 13, 18].…”
Section: Introductionmentioning
confidence: 99%